2007
DOI: 10.1021/bm0702399
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Aqueous Solutions of Microcrystalline Cellulose/Sodium Hydroxide below 0 °C and the Limit of Cellulose Dissolution

Abstract: The aim of the paper is to investigate the structure of solutions of microcrystalline cellulose in NaOH/water mixtures and to determine the limit of cellulose solubility. The binary NaOH/water and the ternary cellulose/NaOH/water phase diagrams in the area of cellulose dissolution (7-10% NaOH below 0 degrees C) are studied by DSC. The NaOH/water binary phase diagram has a simple eutectic behavior. Because of the existence of this eutectic structure, it is possible to measure the influence of the addition of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
112
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 10 publications
5
112
0
4
Order By: Relevance
“…Aside thermodynamic limitations due to the NaOH/AGU ratio needed to solubilize cellulose (Egal et al 2007) and the fast gelation of the solutions (Roy et al 2003), the results reported here show that dissolution proceeds in a complex way that strongly depends on the location of the cellulose chains inside the cell structure.…”
Section: Discussionmentioning
confidence: 75%
“…Aside thermodynamic limitations due to the NaOH/AGU ratio needed to solubilize cellulose (Egal et al 2007) and the fast gelation of the solutions (Roy et al 2003), the results reported here show that dissolution proceeds in a complex way that strongly depends on the location of the cellulose chains inside the cell structure.…”
Section: Discussionmentioning
confidence: 75%
“…The fundamental studies on the preparation of cellulose-NaOH-water solutions and cellulose solubility in NaOH-water, celluloseNaOH-water structure as well as properties and morphology of cellulose films prepared from this solution have been performed by Japanese teams (Kamide et al 1984;Yamashiki et al 1988;Isogai and Atalla 1998;Isogai 1997;Matsui et al 1995). We continued the research in this direction by trying to understand the interactions between cellulose and NaOH and determining the limit of cellulose dissolution in (7-9%) NaOH-water (Egal et al 2007), by studying the flow and gelation of cellulose-NaOHwater solutions (Roy et al 2003) and by preparing ultra-light and highly-porous ''aerocellulose'' through the drying of cellulose-NaOH-water gels in supercritical CO 2 conditions (Gavillon and Budtova 2008). The influence of regeneration conditions like coagulant type and concentration as well as cellulose concentration on the morphology, tensile properties and permeability of porous membranes cast from cellulose-sodium hydroxide solutions have been discussed in (Kuo and Hong 2005;Cao and Tan 2006;Yang et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts have also been done on understanding why the dissolving of cellulose in the alkali aqueous solution needs a precooling process. Solid-state 13 C-NMR (Porro et al 2007), low temperature DSC (Roy et al 2001), small-angle X-ray scattering (Egal et al 2007), and synchrotron radiation microdiffraction (Schoeck et al 2007) studies revealed that the Na-cellulose complex and the hydration of alkali ions formation are the key factors to the dissolving mechanism. The results also showed that the solubilization of cellulose is limited into a very narrow region of 8-9 wt.% NaOH and at temperature of 4°C and below is quit remarkable.…”
Section: Introductionmentioning
confidence: 99%